2019
DOI: 10.1016/j.jsha.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of transcatheter closure of ventricular septal defect using Nit-Occlud Lê ventricular septal defect coil, single-center experience

Abstract: ObjectivesTo assess safety, efficacy and follow-up results of transcatheter closure of ventricular septal defect (VSD) using Nit-Occlud_ Lê VSD Coil (pfm medical, KÖln, Germany).BackgroundTranscatheter VSD closure has achieved encouraging results but more follow-up studies are needed.Patients and methodsBetween January 2012 and December 2013 in the cardiology department, Tanta University Hospital, Tanta, Egypt, 80 patients underwent percutaneous VSD closure using Nit-Occlud_ Lê VSD Coil. Early and mid- term fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…This was the initial study for introducing this device in clinical practice and, therefore, incorporates the learning curve for the operators using this coil. The final closure rates are close to those reported by others [ 6 , 9 , 16 , 20 , 21 , 23 , 25 , 29 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This was the initial study for introducing this device in clinical practice and, therefore, incorporates the learning curve for the operators using this coil. The final closure rates are close to those reported by others [ 6 , 9 , 16 , 20 , 21 , 23 , 25 , 29 ].…”
Section: Discussionsupporting
confidence: 90%
“…The main reason for failure was inadequate periprocedural sizing of the ventricular septal defect. A similar success rate of VSD closure using the Nit-Occlud® Lê VSD coil has been described in later studies [ 11 , 25 ]. These patients were followed over a 3-year period in 18 European centers.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Remarkably, a new small but detectable shunt was again detected in one of our patients with the Nit-Occlud® 3 years after the procedure during pregnancy. This reopening of the shunt might be a result of increased cardiac output and ventricular dilatation during pregnancy [ 7 , 9 , 31 , 32 ]. Therefore, residual shunting appears to be related to the device type and location of the VSD.…”
Section: Discussionmentioning
confidence: 99%
“…The most feared complication of transcatheter VSD closure is cAVB with a reported incidence of 0–6.4% [ 7 , 25 , 28 , 30 , 32 ] and cAVB after surgical VSD closure has been reported with a prevalence of 1–5% [ 16 , 33 35 ]. More current studies have reported cAVB rates between 1.25 and 1.4% for transcatheter VSD closure as a comparable risk after operation [ 9 , 31 , 36 39 ]. According to our data, we observed only 1/149 (rate 0.7%) patient with cAVB for all different VSD devices investigated during > 6 years of follow-up, which is a lower rate than published data to date for interventional and surgical approach.…”
Section: Discussionmentioning
confidence: 99%